Radiotherapy influences local control in patients with desmoplastic melanoma. Issue 9 (18th October 2013) - Strom, Tobin; Caudell, Jimmy J.; Han, Dale; Zager, Jonathan S.; Yu, Daohai; Cruse, C. Wayne; Marzban, Suroosh S.; Messina, Jane L.; Trotti, Andy M.; Sondak, Vernon K.; Rao, Nikhil G.
Abstract : BACKGROUND: Desmoplastic melanoma may have a high risk of local recurrence after wide excision. The authors hypothesized that adjuvant radiotherapy (RT) would improve local control in patients with desmoplastic melanoma, resulting in at least a 10% absolute decrease in local recurrence rate. METHODS: A total of 277 patients from 1989 through 2010 who were treated for nonmetastatic desmoplastic melanoma by surgery with or without adjuvant RT were reviewed. Clinicopathologic and treatment variables were assessed with regard to their role in local control. RESULTS: A total of 113 patients (40.8%) received adjuvant RT. After a median follow‐up of 43.1 months, adjuvant RT was found to be independently associated with improved local control on multivariable analysis (hazards ratio, 0.15; 95% confidence interval, 0.06‐0.39 [ P  < .001]). Among 35 patients with positive resection margins, 14% who received RT developed a local recurrence versus 54% who did not ( P  = .004). In patients with negative resection margins, there was a trend ( P  = .09) toward improved local control with RT. In patients with negative resection margins and traditionally high‐risk features, including a head and neck tumor location, a Breslow depth > 4 mm, or a Clark level V tumor, RT was found to significantly improve local control ( P  < .05). The data from the current study would suggest that patients who would be good candidates for omitting RT included those with negative resection margins, a Breslow depth ≤ 4 mm, and either no perineural invasion present or a non‐head and neck tumor location. CONCLUSIONS: RT for desmoplastic melanoma was independently associated with improved local control. Patients with positive resection margins or deeper tumors appeared to benefit the most from RT, whereas selected low‐risk patients can safely omit RT. Cancer 2014;120:1369–1378 . © 2013 American Cancer Society . Abstract : Radiotherapy for desmoplastic melanoma was found to be independently associated with improved local control. Patients with positive resection margins or deeper tumors appeared to benefit the most from radiotherapy, whereas selected low‐risk patients, including those with negative resection margins and a Breslow depth of 4 mm or less and either no perineural invasion present or a non‐head and neck tumor location, can safely omit radiotherapy.